LIBERAL ARTILLERY IN THE REFORM, OR FROM MELTING BELLS TO MAKE CANNONS (Tzintzun, Revista de Estudios Históricos, 2022)
This article explains how the liberal army established improvised armorers andmelted church bells in the midst of the Reform War to recover lost artillery. Thetechnical aspects of the handcrafted production of cannons and their use andimportance in the war are analyzed. The origin of the popular resistance tolowering bells and the anticlericalism of some sectors of society, which played infavor of the liberals, are also interpreted.
Keywords: artillery; armorers; bells; popular religiosity; popular anticlericalism; liberal Reform in Mexico